Mediating Role of Environmental Attitude Between Consumers’ Satisfaction and Repeat Purchase of Eco-friendly Petrol in Indonesia - Arry Widodo; Nabsiah Abdul Wahid (Jurnal Manajemen Indonesia, 2023)
Indonesia has serious air pollution. The joint effort between the Indonesian government and PT. To minimise pollution problems, Pertamina has introduced eco-friendly petrol known as Pertamax RON 92, targeted at fourwheel vehicle consumers. This study investigates whether environmental attitude mediates consumers' satisfaction and repeat purchase behaviour in consuming Pertamax. A survey of 469 Pertamax consumers in Jakarta petrol stations confirmed that consumers' satisfaction and repeat purchase behaviour are mediated by environmental attitude. The tests carried out between satisfaction and attitude, perspective, repeat purchase, and satisfaction and repeat purchase also found significant relationships between the variables. The results imply the critical roles played by three variables as displayed from the direct and indirect connections. In other words, consumers purchased Pertamax RON 92 because they are satisfied and have a positive environmental attitude. For future promotion, the focus can be emphasised on the quality of eco-friendly petrol. It influences consumers’ satisfaction and continuous education to enhance consumers' positive attitudes toward the environment. This research describes a caring attitude towards the environment stimulated by consumer satisfaction in consuming green innovative products, which has become a highlight of environmental issues in various parts of the world. Keywords— Satisfaction; Environmental Attitude; Repeat Purchase; Eco-friendly